The Relationship Between The Condition Of Latrine Buildings, The Condition Of Waste Water Drainage Channels (SPAL) And The Habit Of Washing Hands With Soap With The Incidence Of Diarrhea In Toddlers In The Working Area Of The Sionom Hudon Timur II Village Health Post, District, Humbang Hasundutan Regency In 2021 - Sipra Barutu (Journal Health of Indonesian, 2023)
The availability of toilets, waste water drainage channels that meet the requirements, as well as clean and healthy living habits such as washing hands with soap are efforts to prevent the increase in the incidence of diarrhea. This study aims to determine the relationship between the condition of latrine buildings, the condition of waste water drainage channels and the habit of washing hands with soap with the incidence of diarrhea in toddlers.in the working area of the Sionom Hudon Timur II village health post, This research is a type of quantitative research, with a research design using a cross-sectional approach. The sample in this study was 59 toddlers in Sion Timur II village using a total sampling technique. Data collection methodscondition of latrine buildings, condition of waste water drainage channels, habit of washing hands with soap and incidence of diarrhea using a questionnaire sheet. The research results used the chi-square test. The results of this study show that the proportion of diarrhea incidents in toddlers is 33.9%. The condition of the latrine building does not meet the requirements 32.2%, SPAL does not meet the requirements 81.4%, the habit of not washing hands with soap is 72.9%. The results of statistical tests related to the incidence of diarrhea in toddlers were the condition of latrine buildings (p=0.001), SPAL (p=0.008),habit of washing hands with soap (p=0.001).Through the results of the analysis, it can be concluded that there is a significant relationship between the condition of latrine buildings, the condition of waste water drainage channels, and the habit of washing hands with soap with the incidence of diarrhea in Sion Timur II village, Parlilitan subdistrict. It is recommended that the community health center, village midwife and community collaborate to improve environmental hygiene and health.